PENGARUH IMPLEMENTASI PROGRAM WIRAUSAHA MAHASISWA (PMW) DAN PROGRAM KREATIVITAS MAHASISWA KEWIRAUSAHAAN (PKM-K) TERHADAP MOTIVASI MAHASISWA BERWIRAUSAHA - Susilo, Heru (FIA UB, 2013)
Abstract: Effect of Implementation of Student Entrepreneurial Program (PMW) and Entrepreneurship Student Creativity Program (PKM-K) Student Motivation Toward Entrepreneurship. Government represented by Ministry of Education and Culture has provided the stimulus for college students to start learning to understand entrepreneurship through Program Wira Usaha (PMW) and Program Kreativitas Mahasiswa Kewirausahaan (PKMK). This stimulation is expected to grow student entrepreneurial spirit and to get creative mindset and can better prepare themselves to face more complex job challenges. Results of the research on college students in the Faculty of Administrative Science shows that students are motivated because they are attracted to the fund that will earned, the other are motivated because of friends, and the rest are really want to be an entrepreneur. Further research showed that of the 34 respondents, they looked fairly good this program, or in the